Ética, direito e ciência no paradigma da complexidade - Valéria Cruz Álvares; Willis Santiago Filho Guerra (EccoS – Revista Científica)
The problems concerning values, which are the issues of ethics and Law, only recover their importance in our age of science when we become aware of the damage that science can cause. So we acknowledge the need for a shift of paradigm, in order to overcome scientific redutionism together with the traditional gap between subject and object of knowledge, toward an holistic approach, as we have in autopoiesis theory.